(untitled) (Sociologisk Forskning, 2015)
Genre stratification and the mass media’s neutralization of the critique of ADHD: A sociology of knowledge perspective This study examines how the Swedish mass media has dealt with the opposition against the neuropsychiatric diagnosis ADHD (Attention Deficit Hyperactivity Disorder). Drawing on empirical data from eight of the largest newspapers in Sweden (n=778 articles) the study focuses on the scientific controversy of DAMP, 2000–2006. DAMP (Dysfunction in Attention, Motor Control and Perception) is a diagnostic term denoting difficulties similar to ADHD, and which was used in Sweden at the time of the controversy. The study uncovers the ideological role played by the mass media during the DAMP-controversy, and demonstrates the significance of genre. While the spokespersons for DAMP/ADHD were given exclusive and systematic access to the news genre, the forum of fact-production in the mass media, the critics of DAMP/ADHD were confined to arguing and expressing their opinions in the debate genre. Based on the various effects of genre differences a comprehensive analytical tool for the sociology of knowledge, called genre stratification, is developed in the study